Skin Epidermis and Adnexa Regrowth Induced by Treatment With Artificial Dermal Template After Full-Thickness Skin Wound. (March 2019) - Li, Binghui; Xue, Hang; Zhao, Xiaobo; Weng, Yuxiong; Li, Gongchi; Wang, Kun; Zhou, Pan; Wu, Youtong; Vankelecom, Hugo; Chen, Jianghai
Full-thickness skin wounds are common accidents. Although healing can be achieved by treatments like autologous skin grafts, donor site morbidity is hardly evitable. In this article, we provide compelling evidence demonstrating that artificial dermal template (ADT)-treated wound healing is achieved by regrowth of skin epidermis as well as adnexa without skin grafts by use of rodent models. First, by fixating a chamber to the wound edge, we confirmed that wound healing was achieved by regeneration instead of contracture. We found highly proliferative cells in adnexa in the newly formed skin. In the distal edge of newly formed skin, we identified immature hair follicles at early developing stages, suggesting they were newly regenerated. Second, we observed that the Lgr5-positive hair follicle stem cells contributed to formation of new hair follicles through a lineage tracing model. Also, Lgr6-positive cells were enriched in distal edge of newly developed skin. Finally, WNT signaling pathway mediators were highly expressed in the new skin epidermis and adnexa, implying a potential role of WNT signaling during ADT treatment-stimulated skin regrowth. Taken together, our findings demonstrated that full skin regrowth can be induced by ADT treatment alone, thus arguing for its wide clinical application in skin wound treatment.